New Trends of Updated Educational System in the Republic of Kazakhstan - Farida, Orazakynkyzy; Gulash, Kochshanova; Karakat, Dalelkyzy; Nurzhan, Saparbayeva; Raikhan, Ozgambayeva; Ulbosyn, Aimbetova (International Journal of Psychosocial Rehabilitation, 2020)
The conducted research has revealed that although monitoring techniques have been used in the education system widely and for a long time, insufficient account has been taken of opportunities emerging from their direct impact on the effectiveness of education quality. In using monitoring as a tool for assessing higher education quality, various problems arise. Monitoring, in this case, is not a universal tool; but if it is adequate to the existing conditions and its results are correctly used, it can essentially improve the quality of the education process and of its outcomes. The article presents the analysis of the components of monitoring as one of management tools for the higher education (HE) system at macro- and micro- levels. The aim of the article is to identify problems of its organization and implementation in the system of professional education on the whole and in higher educational institutions in particular, as well as to analyze the application prospects of monitoring.